Coupled SPH-FEM Simulation Model to Analyze the Mechanism of Single Particle Impact in Abrasive Waterjet Machining - Y. Abdelhameed; Ibrahem Maher; Jiwang Yan; Hassan El-Hofy; Mohsen A. Hassan (Tribology in Industry)
Studying single particle impact is crucial to understanding the erosion mechanism in abrasive waterjet machining (AWJM). In this paper, the finite element method (FEM) and smoothed particle hydrodynamics (SPH) were combined to investigate the mechanism of single particle impact under the waterjet influence. The particle (garnet) and workpiece (Al 7075-T6) were represented by FEM, while the waterjet was discretized using SPH. Linear elasticity and the Johnson-Cook (JC) model were selected to model the abrasive and workpiece materials, respectively. The simulation was conducted in ABAQUS where the effects of particle shape, position, and impact angle on material removal were investigated. The results of the developed model revealed that the erosion mechanism and mechanics significantly differed when considering the waterjet effect. This was primarily attributed to the dynamic phenomena resulting from the waterjet impact, including stagnation zone and drag forces. It was found that the impact angle corresponding to maximum erosion depended on the particle shape and radial position within the jet stream. The presented model has proved its capability since it offers a novel perspective on the single particle impact mechanism by incorporating the realistic dynamic phenomena accompanying the impact in AWJM.